Investments, foreign. ([Australia] : [publisher not identified], 1954)
Includes articles from the period 1954 to 1992. Many articles from the 1960s and 1970s are on US investment in Australia and the debate on restrictions on inflow of foreign capital. Articles from the early 1980s are on Asian property investment and calls to limit overseas investments.
Newspaper cuttings from the Australian press clippings collection covering geographic places, including Australian states, towns and geographical features. Content covers the time period from 1954 to 1992.
Keywords: Investments, Foreign -- Australia; Investments, American -- Australia; International business enterprises -- Australia; Real property -- Foreign ownership; Australian